The Effect of Aquarobic on Physical Fitness Levels - Muhamad Rifki Farid Fauzi; Dede Rohmat Nurjaya; Nida’ul Hidayah; Mulyana (Universitas Negeri Semarang, 2025)
In Indonesia, many industrial companies still pay little attention to the physical fitness of their employees. If physical fitness is not maintained properly, there could be chronic physical illness, which seems to cause middle age to depend on others in their lives, thus affecting their quality of life. Therefore, in order to maintain physical fitness with a small risk of sports injury, it is better to choose water sports because they are safer than sports on land and allow for increased amplitude of movement and energy expenditure for middle age, one of which is aquarobics. Therefore, the researcher aims to examine the effect of aquarobics on the level of physical fitness of industrial employees. This study uses a quantitative approach with an experimental method with a One Group Pretest-Posttest Design research design. The population in this study involved industrial employees in Sindang Palay, Rahayu Village, Bandung Regency, totaling 30 people, then the sample used was 7 people selected using purposive sampling techniques. The instruments used are the Harvard step test, sitting standing from a chair for 30 seconds, sit and reach, time up and go, to find out how much the level of physical fitness is. Based on data analysis through paired t test at Alpa 0.05, it can be concluded that there is a significant effect of aquarobic exercise on physical fitness. Thus because of this significance, it can be known that aquarobics can affect the physical fitness of industrial employees.